ANALYSIS OF BRAND IMAGE AND TRUST TOWARDS TAXPAYER LOYALTY IN LUBUK PAKAM DISTRICT THROUGH TAXPAYER COMMITMENT - Safii; Erwansyah; Yossie Rossanty (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of brand image and trust on taxpayer loyalty with commitment as an intervening variable in taxpayers registered in Lubuk Pakam District. The background of this study departs from the phenomenon of low taxpayer loyalty indicated by formal compliance without being followed by sustainability in tax payments. This study uses a quantitative approach with a survey method on 97 respondents determined by the Slovin formula from a population of 3,875 taxpayers. Data were analyzed using Partial Least Square (PLS) through validity, reliability, R-square, and path analysis tests. The results show that brand image has a positive but insignificant effect on loyalty, while brand image has a positive and significant effect on commitment. Trust is proven to have a positive and significant effect on both loyalty and commitment. In addition, commitment has a positive and significant effect on taxpayer loyalty. The indirect effect test shows that commitment mediates the influence of brand image and trust on taxpayer loyalty. The R-square value of 0.639 for commitment and 0.809 for loyalty indicates that this research model has strong explanatory power. This study concludes that increasing taxpayer loyalty in Lubuk Pakam District is more effective through strengthening commitment, built on positive perceptions of brand image and trust in tax institutions. The results are expected to provide input for tax authorities in formulating public service and communication strategies oriented towards sustainably increasing taxpayer loyalty.